Comparing the clinical efficacy of three surgical methods for cesarean scar pregnancy - Shaoying Zeng; Yang Wang; Ping Ye; Ling Xu; WenLing Han; Feng Li; Chen Tang; Jieli Zhou; Xiaoying Xie (BMC, 2023)
Abstract Background We aimed to compare the clinical efficacy of three surgical methods in the treatment of various types of cesarean scar pregnancy (CSP). Methods Herein, 314 cases of CSP were treated in the department of Obstetrics and Gynecology of the First Affiliated Hospital of Gannan Medical University between June 2017 and June 2020. The patients were divided into three groups based on the treatment received: group A (n = 146; curettage by pituitrin combined with ultrasonic monitoring and hysteroscopy-guided surgery), group B [n = 90; curettage after methotrexate (MTX) injection into the local gestational sac], and group C (n = 78; laparoscopic, transvaginal, and transabdominal cesarean scar resection). These groups were divided into three subgroups (type I, type II, and type III) according to the CSP type of the patients. Results The intraoperative blood loss, length of hospital stay, hospitalization cost, menstrual recovery time, and serum β-HCG normalization time were lower in groups A than in groups B or C with type I, II and III CSP (P < 0.05). Operative efficiency and Successful second pregnancy rate were higher in groups A than in groups B or C with type I and II CSP (P < 0.05). But in type III CSP, the complications were more serious in group A than group C. Conclusions Curettage by pituitrin combined with ultrasonic monitoring and hysteroscopy-guided surgery is an effective and relatively safe treatment for patients with type I and II CSP. Laparoscopic surgery is more suitable for type III CSP.